2016
DOI: 10.1177/0148607116672621
|View full text |Cite
|
Sign up to set email alerts
|

Does Persistent Inflammatory Catabolic Syndrome Exist in Critically Ill Neonates?

Abstract: PICS does exist in a critically ill neonatal population and may be identified using the definition proposed in this study. Infants with PICS displayed metabolic dysregulation, impaired expected growth velocity, and longer length of stay despite no differences in severity scores or diagnosis between the groups. Validation of this work is required, and research into timely identification of infants with PICS is needed to inform whether these infants would benefit from earlier and novel nutrition intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…There is evidence of an association among malnutrition, increased risk of inflammation, and loss of myocardial muscle . Ellis et al described persistent inflammatory catabolic syndrome in cardiac surgical infants and found that it significantly impaired growth velocity . Infants included in the study were able to achieve only 75% of their expected weight gain, and half were classified as failure to thrive .…”
Section: Pathophysiology Of Malnutrition In Pediatric Hfmentioning
confidence: 99%
See 4 more Smart Citations
“…There is evidence of an association among malnutrition, increased risk of inflammation, and loss of myocardial muscle . Ellis et al described persistent inflammatory catabolic syndrome in cardiac surgical infants and found that it significantly impaired growth velocity . Infants included in the study were able to achieve only 75% of their expected weight gain, and half were classified as failure to thrive .…”
Section: Pathophysiology Of Malnutrition In Pediatric Hfmentioning
confidence: 99%
“…Ellis et al described persistent inflammatory catabolic syndrome in cardiac surgical infants and found that it significantly impaired growth velocity . Infants included in the study were able to achieve only 75% of their expected weight gain, and half were classified as failure to thrive . Growth may also be compromised by intestinal malabsorption and dysfunction .…”
Section: Pathophysiology Of Malnutrition In Pediatric Hfmentioning
confidence: 99%
See 3 more Smart Citations